Aspergillus nosocomial infections: do cryptic species found in hospital environment matter? - Sabino, Raquel (2017)
Purpose - Aspergillus is a major threat causing nosocomial infections in immunocompromised patients, especially those subjected to transplantation. Until recently, species identification relief on morphological features. Advances in molecular methods allowed species identification through sequencing of specific genes, allowing high discrimination amongst isolates, which enables the genetic differentiation to species level of morphologically identical isolates. These are the so-called cryptic or sibling species. Different Aspergillus species have different susceptibilities to antifungals and several cryptic species have been described as less susceptible to specific antifungals. Therefore, we addressed the possible influence of hospital environmental isolates in the overall situation of Aspergillus antifungal resistance.